A kind of machine-made sand ultra-high performance concrete and its preparation process

By modifying the machined sand and forming a coating film with a cross-linked network structure, the problem of poor concrete resistance due to machined sand is solved, and the effect of improving the compactness and permeability of concrete is achieved.

CN116573908BActive Publication Date: 2025-02-14HENAN XING BUILDING MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310600280.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-25
Publication Date
2025-02-14
Estimated Expiration
2043-05-25

AI Technical Summary

Technical Problem

The existing concrete containing machine sand has poor anti-permeability due to the sharp and angular grains of machine sand.

Method used

By modifying the machined sand, the modified solution is prepared by mixing chitosan, gelatin and acetic acid solution, wrapped around the surface of the machined sand to form a coating film with a cross-linking network structure, reducing the sharpness of the edges and angles of the surface of the machined sand, and Improve its grading effect in concrete.

Benefits of technology

It improves the density and permeability of concrete, delays the generation of internal dry cracks, and enhances the overall performance of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004248657540000071
    Figure BDA0004248657540000071
  • Figure BDA0004248657540000081
    Figure BDA0004248657540000081
Patent Text Reader

Abstract

The present invention relates to the field of concrete, and in particular to a kind of ultra-high performance concrete of machine-made sand and preparation process, mainly including the following raw materials by weight: 60-90 parts of water, 70-110 parts of cement, 30-50 parts of coarse aggregate, 25-40 parts of modified machine-made sand, 15-25 parts of fly ash, 8-12 parts of reinforcing fiber, 3-5 parts of quicklime, 1-3 parts of iron powder; the preparation method of the modified machine-made sand comprises the following steps: S11: mixing the modified liquid with the machine-made sand to prepare a mixture; the modified liquid is mixed with chitosan, gelatin and acetic acid solution; S12: heating, drying and crushing the mixture obtained in step S11. The present application has the advantage of improving the anti-permeability performance of machine-made sand concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of concrete, and in particular to machine-made sand ultra-high performance concrete and a preparation process thereof. Background Art

[0002] Concrete is a commonly used material in the construction industry in modern society. It is used to build bridges, roads, ports, etc. Therefore, the quality of concrete has an important impact on the quality of building facilities. As a common raw material in concrete preparation, machine-made sand is widely used because of its abundant resources, low production cost and environmental protection. Concrete prepared from machine-made sand is currently widely used in the field of construction.

[0003] After years of use, existing concrete buildings are prone to leakage due to cracks inside the concrete, which causes the buildings to mold and age, requiring a lot of manpower and material resources to repair; therefore, one of the directions to improve the durability of buildings is to improve the anti-penetration performance of concrete.

[0004] In the above-mentioned related technologies, the inventors believe that the existing concrete containing machine-made sand has a slightly poor gradation after being added into the concrete because the machine-made sand particles are sharp and angular, resulting in poor anti-penetration performance of the prepared concrete. Summary of the invention

[0005] In order to improve the anti-permeability performance of machine-made sand concrete, the present application provides a machine-made sand ultra-high performance concrete and a preparation process.

[0006] In the first aspect, the present application provides a machine-made sand ultra-high performance concrete, which adopts the following technical solution:

[0007] A machine-made sand ultra-high performance concrete mainly comprises the following raw materials in parts by weight: 60-90 parts of water, 70-110 parts of cement, 30-50 parts of coarse aggregate, 25-40 parts of modified machine-made sand, 15-25 parts of fly ash, 8-12 parts of reinforcing fiber, 3-5 parts of quicklime, and 1-3 parts of iron powder. The preparation method of the modified machine-made sand comprises the following steps:

[0008] S11: mixing a modified liquid with machine-made sand to prepare a mixture; the modified liquid is a mixture of chitosan, gelatin and acetic acid solution;

[0009] S12: The mixture obtained in step S11 is heated, dried, and crushed.

[0010] By adopting the above technical scheme, water, cement, coarse aggregate, modified machine-made sand, fly ash, reinforcing fiber, quicklime and iron powder are mixed together to prepare concrete. Since the machine-made sand is made by mechanically crushing hard rock, it has relatively sharp edges and corners after processing, and its appearance is generally triangular or polygonal. This makes it so that after the machine-made sand is added to the concrete, more pores are formed inside the concrete, and the gradation is uneven, so that the density of the concrete is insufficient and the anti-penetration performance of the concrete is poor. In the present application, the machine-made sand is modified, and chitosan, gelatin and acetic acid solution are mixed to prepare a modified liquid. The gelatin can react with the amino groups on the chitosan by cross-linking reaction, and the cross-linking reaction can be carried out. The modified liquid reacts with chitosan to produce hydrogen bonds and connect, so that after the prepared modified liquid is wrapped on the surface of the machine-made sand, a dense coating film with a cross-linked network structure is generated after drying, which reduces the sharpness of the edges and corners on the surface of the machine-made sand, so that after the prepared modified machine-made sand is added to the concrete, the grading effect is better and the concrete's anti-permeability is also improved; at the same time, the modified liquid also has a good hydrophilic effect. When the modified machine-made sand is added to the concrete, the modified liquid after the surface is dried can absorb moisture and retain the moisture. When the concrete shrinks due to the excessively fast drying rate, the modified machine-made sand slowly releases moisture to delay the generation of internal drying cracks, thereby improving the density and anti-permeability of the concrete.

[0011] Optionally, the mass ratio of chitosan to gelatin in the modified solution in step S11 is (5-8):(2-4).

[0012] By adopting the above technical scheme, the mass ratio of chitosan to gelatin in the modified liquid is adjusted. When the amount of gelatin added is small, the cross-linking effect between gelatin and chitosan is small and the degree of cross-linking is insufficient, so that after the prepared modified liquid is coated on the surface of the machine-made sand, the strength of the coating formed by drying is insufficient, and it is easy to crack during the mixing process, affecting the grading effect between the machine-made sands, thereby reducing the anti-penetration performance of the prepared concrete; however, when the amount of gelatin added is large, the gelatin is brittle and has low strength, which reduces the mechanical properties of the coating formed by drying the modified liquid, and the coating is easy to crack during the mixing process of the modified machine-made sand, thereby reducing the density of the concrete, thereby reducing the anti-penetration performance of the concrete.

[0013] Optionally, before mixing the modified liquid with the machine-made sand in step S11, sodium polyphosphate is added to the modified liquid, and the mixture is heated and stirred after mixing; the mass ratio of the sodium polyphosphate to chitosan is (1-2):(8-10).

[0014] By adopting the above technical scheme, sodium polyphosphate can provide polyanions when mixed with the modifying liquid. The positive charge carried by the protonated free amino groups in chitosan can be cross-linked with the polyanions through the electrostatic attraction between molecules or within molecules, so that the cross-linking density of the coating formed after the modifying liquid is dried is increased, and the mechanical properties of the coating are improved; at the same time, sodium polyphosphate can form a small amount of nanoparticles with chitosan, and the nanoparticles can play a role in strengthening and toughening the coating formed by the modifying liquid, further improving the mechanical properties of the formed coating, and then improving the anti-penetration performance of the prepared concrete.

[0015] Optionally, the reinforcing fibers are composed of steel fibers and polyvinyl alcohol fibers in a mass ratio of (3-5):(2-3).

[0016] By adopting the above technical scheme, steel fibers and polyvinyl alcohol fibers are compounded, and the steel fibers are interlaced and distributed in the concrete to form a network skeleton structure. The polyvinyl alcohol fibers can be inserted into the network skeleton structure formed by the steel fibers to encrypt the network skeleton structure; when cracks just begin to appear in the concrete, the steel fibers strengthen the concrete through the bonding force between the steel fibers and the concrete, thereby preventing the occurrence of cracks; when the cracks in the concrete continue to increase, the bonding force between the steel fibers and the concrete decreases, and the polyvinyl alcohol fibers can exert their toughening and crack prevention effects through their own deformation, thereby further preventing the cracking of the concrete; through the compounding effect of steel fibers and polyvinyl alcohol fibers, the occurrence of concrete cracks is reduced together, and the anti-penetration performance of the concrete is improved.

[0017] Optionally, the polyvinyl alcohol fiber is pretreated before use, and the pretreatment comprises the following steps:

[0018] 1) melting paraffin to prepare paraffin liquid, and applying the paraffin liquid to the outside of the polyvinyl alcohol fiber to prepare an intermediate;

[0019] 2) Cooling and crushing the intermediate obtained in step 1).

[0020] By adopting the above technical scheme, since the polyethanol fibers are relatively soft, after adding them into concrete, they are easy to be entangled with each other and agglomerated in the concrete, making the density inside the concrete uneven, affecting the anti-penetration performance of the concrete; by applying paraffin liquid to the outside of the polyvinyl alcohol fiber, after cooling, the molding and fixing effect of the paraffin is performed, so that the pretreated polyvinyl alcohol fiber has a certain rigidity, and it is not easy to be entangled and agglomerated after adding it into the concrete, thereby improving the dispersibility of the polyvinyl alcohol fiber in the concrete; at the same time, since the preparation raw materials of the concrete contain iron powder and quicklime, the concrete can release heat inside during the mixing and drying process, so that the paraffin on the outside of the pretreated polyvinyl alcohol fiber melts, and the polyvinyl alcohol fiber recovers its toughness after the paraffin melts, which can play a good strengthening and toughening effect on the concrete; at the same time, the molten paraffin can flow into the gaps of the concrete, seal the cracks generated during the drying process of the concrete, improve the density of the concrete, and then improve the anti-penetration performance of the concrete.

[0021] Optionally, the iron powder is immersed in a silk fibroin solution before use, taken out, dried, and crushed.

[0022] By adopting the above technical solution, since iron powder is prone to oxidation reaction when exposed to air, the iron powder is immersed in silk fibroin liquid before use. Since the silk fibroin liquid has good film-forming properties after drying, a silk fibroin film can be generated to wrap the iron powder, thereby slowing down the oxidation rate of the iron powder when exposed to air. When the iron powder wrapped by the silk fibroin film is added to the interior of concrete, the silk fibroin film can play a slow-release role through the effect of water absorption and swelling, so that the iron powder slowly contacts with water and air, undergoes oxidation reaction, and slowly releases heat, thereby avoiding excessive heat release, which causes excessive drying and shrinkage inside the concrete to cause cracks, thereby improving the anti-penetration performance of the concrete.

[0023] Optionally, the iron powder is immersed in a silk fibroin solution, dried, crushed, and then irradiated under ultraviolet light before use.

[0024] By adopting the above technical scheme, the silk fibroin liquid on the surface of the iron powder is irradiated with ultraviolet light, and the ultraviolet light increases the oxygen element on the surface of the silk fibroin and reduces the carbon element, and also increases the carbonyl and carboxyl groups on the surface of the silk fibroin film formed by the silk fibroin liquid. Since the carbonyl and carboxyl groups are both hydrophilic groups, the hydrophilicity of the silk fibroin film can be improved. After being added to concrete, it can absorb water, so that the iron powder contacts with water and undergoes an oxidation reaction to release heat, which promotes the melting of paraffin, thereby reducing cracks in the concrete and improving the anti-penetration performance of the concrete.

[0025] Optionally, the ultraviolet light irradiation time is 10-40 minutes.

[0026] By adopting the above technical scheme, when the ultraviolet light irradiation time is short, the degree of molecular chain breakage on the surface of the silk fibroin membrane is insufficient, the free radicals generated on the surface of the silk fibroin membrane are less, the hydrophilic carbonyl groups generated by the combination of free radicals and oxygen are less, the hydrophilicity of the silk fibroin membrane is insufficient, and the oxidation heat release of the iron powder in the later stage is affected; however, when the ultraviolet light irradiation time is too long, since the energy of the ultraviolet light is greater than the energy required for the rupture of the chemical bonds of the silk fibroin macromolecules, the long-term irradiation causes too many chemical bonds on the surface of the silk fibroin to break, and the mechanical strength of the silk fibroin membrane formed after the silk fibroin liquid is dried decreases, so that the iron powder is easy to release heat prematurely in the concrete, and the slow-release effect on the iron powder is lost, thereby affecting the anti-penetration performance of the prepared concrete.

[0027] In a second aspect, the present application provides a process for preparing ultra-high performance concrete using machine-made sand:

[0028] A preparation process of machine-made sand ultra-high performance concrete mainly includes the following steps:

[0029] S1: Mix cement, coarse aggregate, modified machine-made sand, fly ash and reinforcing fiber to prepare a dry mix;

[0030] S2: adding water, quicklime and iron powder to the dry mix prepared in step S1, and mixing them evenly to prepare concrete slurry;

[0031] S3: solidifying and curing the concrete slurry prepared in step S2.

[0032] By adopting the above technical scheme, cement, coarse aggregate, modified machine-made sand, fly ash and reinforcing fiber are first mixed to prepare a dry mix, so that the reinforcing fiber can be evenly dispersed in other raw materials, reducing the agglomeration of the reinforcing fiber caused by cement hydration; then, by mixing water with the dry mix, the cement increases the viscosity of the slurry under the action of hydration, and the raw materials in the concrete are bonded. At the same time, by modifying the machine-made sand, the sharpness of the surface edges of the machine-made sand is reduced, the gradation of the modified machine-made sand in the concrete is improved, the density of the concrete is improved, and the anti-penetration performance of the concrete is improved.

[0033] In summary, this application has the following beneficial effects:

[0034] The present application adds machine-made sand to the raw materials for preparing concrete, modifies the machine-made sand, mixes and cross-links chitosan and gelatin in an acetic acid solution, forms a modified film to coat the surface of the machine-made sand, reduces the sharpness of the surface of the machine-made sand, makes the modified machine-made sand more graded, reduces the pores in the prepared concrete, improves the density of the concrete, and further improves the anti-penetration performance of the concrete. DETAILED DESCRIPTION

[0035] The present application is further described in detail below with reference to the embodiments and comparative examples;

[0036] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0037] Preparation Example

[0038] Modified machine-made sand preparation example 1

[0039] The preparation method of modified machine-made sand in this preparation example comprises the following steps:

[0040] S11: taking a mixing barrel, placing a modified liquid in the mixing barrel, placing machine-made sand in the modified liquid, and mixing them evenly to prepare a mixture; the modified liquid used is a mixture of chitosan, gelatin and acetic acid solution; the mass fraction of acetic acid in the acetic acid solution used is 4%; the mass ratio of chitosan to gelatin used is 5:4; the mass ratio of chitosan to acetic acid solution used is 1:10;

[0041] S12: The mixture obtained in step S11 is heated in a water bath at 50° C. for 20 min, dried, and crushed.

[0042] Modified machine-made sand preparation example 2

[0043] The difference between the preparation method of modified machine-made sand in this preparation example and that in the modified machine-made sand preparation example 1 is that the mass ratio of chitosan to gelatin in the modification liquid used in step S11 is 8:2.

[0044] Modified machine-made sand preparation example 3

[0045] The difference between the preparation method of modified machine-made sand in this preparation example and that in the modified machine-made sand preparation example 1 is that the mass ratio of chitosan to gelatin in the modification liquid used in step S11 is 7:3.

[0046] Modified machine-made sand preparation example 4

[0047] The difference between the preparation method of modified machine-made sand in this preparation example and that in the modified machine-made sand preparation example 3 is that in step S11, sodium polyphosphate is added to the modifying liquid before the modifying liquid and the machine-made sand are mixed; the mass ratio of the sodium polyphosphate to chitosan used is 1.5:9.

[0048] Example

[0049] Example 1

[0050] The raw materials for preparing the machine-made sand ultra-high performance concrete in this embodiment mainly include: 60kg of water, 70kg of cement, 30kg of coarse aggregate, 25kg of modified machine-made sand, 15kg of fly ash, 8kg of reinforcing fiber, 3kg of quicklime, and 1kg of iron powder; the coarse aggregate used is crushed stone; the cement used is silicate cement; the modified machine-made sand used is prepared in the modified machine-made sand preparation example 1; the reinforcing fiber used is composed of steel fiber and polyvinyl alcohol fiber in a mass ratio of 3:3;

[0051] The preparation process of machine-made sand ultra-high performance concrete in this embodiment mainly includes the following steps:

[0052] S1: Take a mixing barrel, put the above-mentioned weight of cement, coarse aggregate, modified machine-made sand, fly ash, and reinforcing fiber into the mixing barrel, mix them evenly to prepare a dry mix;

[0053] S2: adding the above-mentioned weight of water, quicklime and iron powder to the dry mix prepared in step S1, and mixing them evenly to prepare concrete slurry;

[0054] S3: solidifying and curing the concrete slurry prepared in step S2.

[0055] Example 2

[0056] The preparation process of the machine-made sand ultra-high performance concrete in this embodiment is different from that in Example 1 in that the raw materials used mainly include: 90 kg of water, 110 kg of cement, 50 kg of coarse aggregate, 40 kg of modified machine-made sand, 25 kg of fly ash, 12 kg of reinforcing fiber, 5 kg of quicklime, and 3 kg of iron powder.

[0057] Example 3

[0058] The preparation process of the machine-made sand ultra-high performance concrete in this embodiment is different from that in Example 1 in that the raw materials used mainly include: 70 kg of water, 90 kg of cement, 40 kg of coarse aggregate, 32 kg of modified machine-made sand, 20 kg of fly ash, 10 kg of reinforcing fiber, 4 kg of quicklime, and 2 kg of iron powder.

[0059] Example 4

[0060] The difference between the preparation process of machine-made sand ultra-high performance concrete in this embodiment and that in Embodiment 3 is that the reinforcing fiber used in step S1 is composed of steel fiber and polyvinyl alcohol fiber in a mass ratio of 5:2.

[0061] Example 5

[0062] The difference between the preparation process of machine-made sand ultra-high performance concrete in this embodiment and that in Embodiment 3 is that the reinforcing fiber used in step S1 is composed of steel fiber and polyvinyl alcohol fiber in a mass ratio of 4:2.5.

[0063] Example 6

[0064] The preparation process of machine-made sand ultra-high performance concrete in this embodiment is different from that in Embodiment 5 in that the polyvinyl alcohol fiber in the reinforcing fiber used in step S1 is pretreated before use, and the pretreatment includes the following steps:

[0065] 1) taking a preparation barrel, placing paraffin in the preparation barrel, heating the paraffin to melt the paraffin to prepare paraffin liquid, and applying the paraffin liquid on the surface of the polyvinyl alcohol fiber to prepare an intermediate;

[0066] 2) Cooling the intermediate obtained in step 1) to obtain.

[0067] Example 7

[0068] The preparation process of machine-made sand ultra-high performance concrete in this embodiment is different from that in Embodiment 6 in that the iron powder used in step S2 is immersed in a silk fibroin solution for 10 minutes before use, and then taken out, dried and crushed; the silk fibroin solution used is prepared by mixing silk fibroin and 1-butyl-3-methylimidazole acetate ionic liquid in a mass ratio of 1:6.

[0069] Example 8

[0070] The preparation process of the machine-made sand ultra-high performance concrete in the embodiment is different from that in Example 7 in that the iron powder used in step S2 is immersed in the silk fibroin solution for 10 minutes before use, taken out, dried and crushed, and then irradiated under ultraviolet light for 10 minutes before mixing with other raw materials.

[0071] Example 9

[0072] The preparation process of the machine-made sand ultra-high performance concrete in the embodiment is different from that in the embodiment 8 in that the iron powder used in step S2 is immersed in the silk fibroin solution and then irradiated under ultraviolet light for 40 minutes before use.

[0073] Example 10

[0074] The preparation process of the machine-made sand ultra-high performance concrete in the embodiment is different from that in the embodiment 8 in that, after the iron powder used in step S2 is immersed in the silk fibroin solution, the irradiation time under ultraviolet light is 25 minutes.

[0075] Embodiment 11

[0076] The preparation process of the machine-made sand ultra-high performance concrete in the embodiment is different from that in Example 10 in that the modified machine-made sand used in step S1 is prepared in the modified machine-made sand preparation example 2.

[0077] Example 12

[0078] The preparation process of the machine-made sand ultra-high performance concrete in the embodiment is different from that in Example 10 in that the modified machine-made sand used in step S1 is prepared in the modified machine-made sand preparation example 3.

[0079] Embodiment 13

[0080] The difference between the preparation process of the machine-made sand ultra-high performance concrete in the embodiment and that in the embodiment 10 is that the modified machine-made sand used in step S1 is prepared in the modified machine-made sand preparation example 4.

[0081] Comparative Example

[0082] Comparative Example 1

[0083] The preparation process of the ultra-high performance concrete with machine-made sand in this comparative example is different from that in Example 1 in that the modified machine-made sand used is commercially available machine-made sand, the brand of the machine-made sand used in this comparative example is Fuguo, and the particle size is 120 mesh.

[0084] Comparative Example 2

[0085] The difference between the preparation process of the machine-made sand ultra-high performance concrete in this comparative example and that in Example 1 is that the modified liquid used in the preparation method of the modified machine-made sand in this comparative example is a mixture of chitosan and acetic acid solution in a mass ratio of 1:10.

[0086] Comparative Example 3

[0087] The difference between the preparation process of the machine-made sand ultra-high performance concrete in this comparative example and that in Example 1 is that the modified liquid used in the preparation method of the modified machine-made sand in this comparative example is a mixture of gelatin and acetic acid solution in a mass ratio of 1:10.

[0088] Detection Methods

[0089] According to the preparation process of the ultra-high performance concrete with machine-made sand in Examples 1-13 and Comparative Examples 1-3, machine-made sand concrete was prepared, and cured at 25° C. for 28 days as experimental samples. The experimental samples were tested according to the water penetration resistance test in GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", with a sample size of 150 mm*100 mm, a penetration pressure of 4 MPa, and a pressurization time of 48 h. The water seepage height (mm) of the experimental samples prepared in the above embodiments and comparative examples was detected, and the data were recorded to obtain Table 1;

[0090] Table 1 Water seepage height of machine-made sand concrete prepared in Examples 1-13 and Comparative Examples 1-3

[0091]

[0092]

[0093] It can be seen from the combination of Examples 1-6, Comparative Examples 1-3 and Table 1 that the machine-made sand is modified before use, and a modified liquid is prepared by mixing chitosan, gelatin and acetic acid solution to wrap the machine-made sand. The chitosan and gelatin are cross-linked to form a coating film that is coated on the outside of the machine-made sand, thereby reducing the sharpness of the machine-made sand and improving the gradation of the machine-made sand in the concrete, thereby improving the density of the concrete and the water resistance. At the same time, the mass ratio of the steel fiber and the polyvinyl alcohol fiber in the reinforcing fiber in the concrete is adjusted so that after the steel fiber forms a supporting skeleton, the polyvinyl alcohol fiber can be inserted between the steel fibers, thereby improving the density and mechanical properties of the concrete, thereby improving the water resistance of the machine-made sand concrete. The polyvinyl alcohol fiber is pretreated and wrapped with paraffin to reduce the entanglement and agglomeration of the polyvinyl alcohol fiber in the concrete, and the exothermic effect of the lime and iron powder in the concrete causes the paraffin to melt and seal the gaps in the concrete, thereby further improving the density of the concrete and the water resistance of the concrete.

[0094] It can be seen from Examples 7-10 and Table 1 that by adding iron powder to the raw materials for preparing concrete, the iron powder is oxidized and releases heat, thereby accelerating the melting of paraffin on the surface of the polyvinyl alcohol fiber in the concrete; by wrapping the silk fibroin liquid on the surface of the iron powder, the silk fibroin liquid has a slow-release effect on the iron powder after drying, so that the heat release rate of the iron powder in the concrete is more uniform, and the generation of gaps in the concrete caused by local overheating is reduced; by immersing the iron powder in the silk fibroin liquid and then irradiating it with ultraviolet light, and adjusting the irradiation time, the hydrophilicity of the silk fibroin film formed after the silk fibroin liquid is dried is improved, and after being added to the concrete, the iron powder absorbs moisture so that it can undergo an oxidation reaction, and at the same time has a slow-release effect on the iron powder, thereby promoting the solidification of the concrete;

[0095] Combining Implementation 11-13 and Table 1, it can be seen that by adjusting the mass ratio of chitosan and gelatin in the preparation process of modified machine-made sand, chitosan and gelatin can form a coating film after cross-linking and drying. The coating film has good mechanical properties and hydrophilic properties. It retains moisture by absorbing water and slowly releases it during the drying process of concrete, thereby reducing cracks in the concrete caused by drying shrinkage and improving the density and anti-penetration performance of the concrete; and by adding sodium polyphosphate, sodium polyphosphate is cross-linked with chitosan to form nanoparticles, which strengthens and toughens the coating film, improves the effect of the modified machine-made sand on improving the density of concrete, and thereby improves the anti-penetration performance of the prepared concrete.

[0096] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A machine-made sand ultra-high performance concrete, characterized in that: The raw materials mainly include the following parts by weight: 60-90 parts of water, 70-110 parts of cement, 30-50 parts of coarse aggregate, 25-40 parts of modified machine-made sand, 15-25 parts of fly ash, 8-12 parts of reinforcing fiber, 3-5 parts of quicklime, and 1-3 parts of iron powder; the preparation method of the modified machine-made sand includes the following steps: S11: mixing a modified liquid with machine-made sand to prepare a mixture; the modified liquid is a mixture of chitosan, gelatin and acetic acid solution; S12: heating, drying and crushing the mixture obtained in step S11; The mass ratio of chitosan to gelatin in the modified solution in step S11 is (5-8):(2-4); the mass ratio of chitosan to acetic acid solution is 1:10; In step S11, before the modified liquid is mixed with the machine-made sand, sodium polyphosphate is added to the modified liquid; the mass ratio of the sodium polyphosphate to chitosan is (1-2):(8-10); The reinforcing fibers are composed of steel fibers and polyvinyl alcohol fibers in a mass ratio of (3-5):(2-3); The polyvinyl alcohol fiber is pretreated before use, and the pretreatment comprises the following steps: 1) melting paraffin to prepare paraffin liquid, and applying the paraffin liquid to the outside of the polyvinyl alcohol fiber to prepare an intermediate; 2) cooling and crushing the intermediate obtained in step 1); The iron powder is immersed in the silk fibroin solution before use, taken out, dried, and crushed; and irradiated under ultraviolet light.

2. The machine-made sand ultra-high performance concrete according to claim 1, characterized in that: The ultraviolet light irradiation time is 10-40 minutes.

3. A process for preparing machine-made sand ultra-high performance concrete according to claim 1, characterized in that: The main steps are as follows: S1: Mix cement, coarse aggregate, modified machine-made sand, fly ash and reinforcing fiber to prepare a dry mix; S2: adding water, quicklime and iron powder to the dry mix prepared in step S1, and mixing them evenly to prepare concrete slurry; S3: solidifying and curing the concrete slurry prepared in step S2.

Citation Information

Patent Citations

  • Machine-made sand self-compacting concrete and preparation method thereof

    CN111187040A